Analisis kritik feminisme terhadap bahasa dan tampilan iklan produk kosmetik pemutih - Melania Priska Mendrofa (SAGA: Journal of English Language Teaching and Applied Linguistics, 2020)
The language used in advertisements can reflect social and cultural perspectives. Specific words and sentences used by a cosmetic company can attract consumers to buy and consume a product. The language can also change people's perspective about life and the way they experience it. Cosmetic products have changed women's perspective toward the standard of beauty. The beauty standard is submitted through the persuasive language and the display of beautiful models in the advertisements. It is a common issue that the concept of being a beautiful woman is to have white and glowing skin. Because of this, women buy and use many whitening products to beautify themselves. The language of advertisement 'colonizes' women and kills the concept of a woman's nature. It subordinates some women who keep their natural looks by not using any whitening products. However, women should be aware of this problem and not be affected by the language of advertisement so that they can accept themselves for who they are. Feminist critical discourse analysis helps this research to analyze and criticize the beauty standard that has been imposed on women through the language. In the end, women's awareness is needed to resist the beauty standard as a gender stereotype constructed by society.